Rigoletto - Verdi, Giuseppe 1813-1901 ([San José, Costa Rica] : [editor no identificado], 2004)
Presenta la puesta en escena en el Teatro Nacional de la ópera Rigoletto de Giussepe Verdi
Compañía Lírica Nacional; Giancarlo Guerrero, director musical; Alejandro Chacón, dirección escénica; elenco: Fitzgerald Ramos, María Marta López, Ernesto Rodríguez, Francisco Santiago, Raquel Ramírez, José Arturo Chacón, Joaquín Yglesias, Marvin Hernández, Gustavo Hernández, Glenda Juárez, Mercedes Sánchez, Ivette Rojas
Keywords: OPERAS; DRAMATIZACIONES